Probing the structures of gas-phase rhodium cluster cations by far-infrared spectroscopy. - Harding, D; Gruene, P; Haertelt, M; Meijer, G; Fielicke, A; Hamilton, S; Hopkins, W; Mackenzie, S; Neville, S; Walsh, T (AIP Publishing, 2010)
The geometric structures of small cationic rhodium clusters Rh(n)(+) (n = 6-12) are investigated by comparison of experimental far-infrared multiple photon dissociation spectra with spectra calculated using density functional theory. The clusters are found to favor structures based on octahedral and tetrahedral motifs for most of the sizes considered, in contrast to previous theoretical predictions that rhodium clusters should favor cubic motifs. Our findings highlight the need for further development of theoretical and computational methods to treat these high-spin transition metal clusters.